Analytical Techniques in Pharmaceutical and Biomedical Analysis - Główka, Franciszek; Karaźniewicz-Łada, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is a collection of research topics on developing analytical and bioanalytical methods for isolation, identification, and determination of substances in biomedical and pharmaceutical matrices. Special attention is given to advancements in sample preparation, separation techniques and novel detection methods of small molecules, peptides, and monoclonal antibodies. The presented analytical methods exhibit several applications, including pharmacokinetic studies, therapeutic drug monitoring, microdialysis, toxicology, disease screening or drug stability study. Two comprehensive review articles were also presented on applying capillary electrophoresis to analyze bioactive compounds in herbal matrices.